Exploring the Impact of Maternal Multi-Nutrient Deficiencies on Fetal Growth: Insights from a Primary Care Pregnancy Cohort - Fenti Dewi Pertiwi; Tika Noor Prastia; Resty Jayanti; Yenny Rohmaeni (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: This study aims to examine the impact of nutritional deficiencies during pregnancy on fetal development by analyzing the relationship between nutritional status and prenatal fetal development. METHODOLOGY: This cohort design study was conducted from April to August 2025 with a sample of 92 pregnant women from all health centres in Bogor City Indonesia. The purposive sampling technique was used to determine the sample with strict inclusion and exclusion criteria. The study variables were maternal age, body mass index, and estimated fetal weight. Several tests were used for data analysis, including ANOVA, the Kruskal–Wallis test, and linear regression. RESULTS: The findings revealed significant differences in calcium intake (82.6%), iron (91.3%), and protein (54.3%). Between the MMA and IFA groups, there was a significant difference in calcium intake, with p-values of 0.033 and 0.024, respectively. These findings confirm that calcium intake is crucial for fetal growth. Further analysis showed that fetal weight increased significantly in the MMS group, with a ? value of 3383.64 and a p-value of 0.027. CONCLUSION: This study confirms that calcium has a crucial role in fetal development, especially in the MMS group.